An understanding of communities of singers in the context of a funeral ceremony in Bontoc, Mountain Province, Philippines - De Vera, Christine May (May 2010.)
The study focuses on an ethnography of two communities of singers in Bontoc, Mt. Province namely, a community of contemporary singers called Tokwifi and a community of traditional singers. It describes the formation, role, repertoire and cultural orientation of two communities of singers in the context of a funeral ceremony held in December 2006.
Keywords: Music -- Philippines -- Bontoc, Mountain Province -- History and criticism